DEVELOPING MARITIME ENGLISH PREPARATION TEST BY USING FLASH APPLICATION - Aprillina, Aprillina; Abimanto, Dhanan; Oktavia, Ariana (UNIMAR AMNI Semarang, 2024)
This study aimed at developing of teaching maritime English as English for Specific Purpose especially in conducting Maritime English Preparation Test. The purpose of this study is to find out the problems of maritime students’ in learning Maritime English and describe how the product will be developed. It is also intended to investigate how effective of MEPT for improving students’ achievement for learning maritime English. This study is Research and Development (R and D) and It was adapted from Borg and Gall (1983) and Sugiyono (2009) as the basis of conducting this research. There are Problem arise, Need analysis, Design the concept of Maritime English Preparation Test, Preliminary Test, Expert judgment, product revision, field test and final product of Maritime English Preparation Test by using flash application. The type of the test consisted of some of the aspects such as grammar, pronunciation, listening, vocabularies drilling. I used multiple choice tests as the treatment in order to find out the effectiveness of the product toward the students’ achievement. The aspect of the test item has already designed mixed randomly by the computer program. From the result of the research analysis showed that the product was effective to improve students’ score for Maritime English Test.